2020
DOI: 10.1002/cbic.202000711
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Signal Amplification by Reversible Exchange of Selective PyFALGEA Oligopeptide Ligands Towards Epidermal Growth Factor Receptors

Abstract: The biorelevant PyFALGEA oligopeptide ligand, which is selective towards the epidermal growth factor receptor (EGFR), has been successfully employed as a substrate in magnetic resonance signal amplification by reversible exchange (SABRE) experiments. It is demonstrated that PyFALGEA and the iridium catalyst IMes form a PyFALGEA:IMes molecular complex. The interaction between PyFALGEA:IMes and H2 results in a ternary SABRE complex. Selective 1D EXSY experiments reveal that this complex is labile, which is an es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 36 publications
0
25
0
1
Order By: Relevance
“…[7] Thesubstrate scope of SABRE has,therefore, been most commonly illustrated for molecules with N-donor sites that readily ligate to the iridium center. This approach has been extended to pyridine-tagged biocompatible molecular frameworks,i ncluding oligopeptides [100,101] and glycine. [102] SABRE can involve high symmetry catalysts such as [Ir(H) 2 (IMes)(py) 3 ]Cl with chemically equivalent hydride ligands.T heir magnetic inequivalence is responsible for polarization flow.…”
Section: Phip Of Aas By Sabrementioning
confidence: 99%
“…[7] Thesubstrate scope of SABRE has,therefore, been most commonly illustrated for molecules with N-donor sites that readily ligate to the iridium center. This approach has been extended to pyridine-tagged biocompatible molecular frameworks,i ncluding oligopeptides [100,101] and glycine. [102] SABRE can involve high symmetry catalysts such as [Ir(H) 2 (IMes)(py) 3 ]Cl with chemically equivalent hydride ligands.T heir magnetic inequivalence is responsible for polarization flow.…”
Section: Phip Of Aas By Sabrementioning
confidence: 99%
“…[7] SABRE wurde daher am häufigsten für Moleküle mit N-Donorstellen veranschaulicht, die leicht an Iridium ligieren. Dieser Ansatz wurde auf Pyridin-markierte biokompatible molekulare Gerüste erweitert, darunter Oligopeptide [100,101] und Glycin. [102] SABRE kann hochsymmetrische Katalysatoren wie [Ir(H) 2 (IMes)(py) 3 ]Cl mit chemisch äquivalenten Hydridliganden beinhalten.…”
Section: Angewandte Chemieunclassified
“…PHIP experiments were successfully employed for the detailed investigation of mechanistic problems in organic and inorganic synthesis [19][20][21], for monitoring chemical processes in microreactors, [22][23][24] in time-domain detected experiments [25,26], or in field-cycling [27,28] and ultra-low-field NMR experiments [29][30][31]. They were employed for hyperpolarization of amino acids and peptides [32][33][34][35][36][37][38] and in MRI [39][40][41][42][43][44][45][46][47]. To prolong the application window of PHIP, which is limited by the lifetime of the hyperpolarization, it is advantageous to transfer the hyperpolarization from the hyperpolarized protons to spin-1/2 X-nuclei such as 13 C. Glöggler et al [48,49] reported a pulsed experiment, which can nearly completely transfer the hyperpolarization from the protons to the 13 C. The Side Arm Hydrogenation (PHIP-SAH) 50,51 protocol greatly expanded the range of PHIPpolarizable molecules, which allowed for the hyperpolarization and subsequent in vivo detection of 13 C-labeled pyruvate and its metabolic product lactate in a 1T MRI scanner [52].…”
Section: Introductionmentioning
confidence: 99%